IKZF1/3 and CRL4 (CRBN) E3 ubiquitin ligase mutations and resistance to immunomodulatory drugs in multiple myeloma - Barrio, Santiago; Munawar, Umair; Zhu, Yuan Xiao; Giesen, Nicola; Shi, Chang-Xin; Viá, Matteo Da; Sanchez, Ricardo; Bruins, Laura; Demler, Theresa; Müller, Nicole; Haertle, Larissa; Garitano, Andoni; et al. (Haematologica, 2020)
Cereblon (CRBN), a target of immunomodulatory drugs (IMiD), forms the CRL4CRBN E3 ubiquitin ligase (CRL4) complex with DDB1, CUL4B and ROC1.[1][1],[2][2] Under the influence of IMiD, CRL4 polyubiquitinates and thus depletes the transcription factors IKZF1 and IKZF3, resulting in cytotoxicity to